(untitled) (Current Horticulture, 2024)
The study was carried out on the effect of physical, chemical and biological treatments on carrot (Daucus carota L.) for enhancing shelf-life during post-harvest processing at Department . of Food Process Engineering., Agricultural Engieering college & Research Institute, Tamil Nadu Agricultural University, Coimbatore. The most significant changes in post-harvest quality were weight loss, bitterness, bacterial deterioration, rooting and sprouting. Losses in carrots are due to Sclerotinia rot, Botrytis rot, Bacterial soft rot (Erwinia sp.) and sour rot (Geotrichum sp.). The physical, chemical, biological and combination of these methods were studied. Among the different methods, combination of chlorination and ozonization during washing followed by application of Lactobacillus plantarum 020 at the rate of 10 ml / litre of wash water was more effective. Carrots processed with the treatment had a shelf-life of six days under normal room temperature whereas shelf-life of untreated carrots was two days under normal room temperature.